Enhancing Group Leader Work Performance in Mining Company: The Role of Leadership Styles, Work Engagement and Motivation - Ahmad Ulin Nuha; Mufid Rosichin; Muhammad Indrik; Anita Maharani (PT Mattawang Mediatama Solution, 2024)
The purpose of this study is to investigate the impact of leadership and motivation on the job performance of new group leaders at Pama using work engagement as a moderating variable. A variety of literatures are utilised to describe the interactions between leadership style, work engagement, motivation, and job performance. This is a quantitative research approach, with the study object being a mining business and the unit of analysis being the group leader. Researchers employed the PLS-SEM technique and SMART-PLS software to analyse the data collected from the distribution of the formulary questionnaire. The findings of this investigation demonstrate that a number of hypotheses are validated while others are not. This study's management implication is to advocate the execution of a few supported hypotheses.